Real-World Concurrency. - CANTRILL, BRYAN; BONWICK, JEFF (Communications of the ACM, 2008)
The article discusses the impact on computer software development of the proliferation of concurrency. The term concurrency can be defined as several computational processes which are executing at the same time and potentially interacting with each other, the article states. Topics include computer code that needs to be highly parallel and explicitly multithreaded, that writing parallel code remains somewhat of a mysterious art, and implementation techniques for developing a highly parallel system. Also discussed is code that should achieve concurrency without explicit parallelism.